2013
DOI: 10.1164/rccm.201304-0803oc
|View full text |Cite
|
Sign up to set email alerts
|

S100A8/A9 Proteins Mediate Neutrophilic Inflammation and Lung Pathology during Tuberculosis

Abstract: Rationale: A hallmark of pulmonary tuberculosis (TB) is the formation of granulomas. However, the immune factors that drive the formation of a protective granuloma during latent TB, and the factors that drive the formation of inflammatory granulomas during active TB, are not well defined. Objectives: The objective of this study was to identify the underlying immune mechanisms involved in formation of inflammatory granulomas seen during active TB. Methods: The immune mediators involved in inflammatory granuloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
224
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 211 publications
(270 citation statements)
references
References 45 publications
27
224
0
3
Order By: Relevance
“…We have previously demonstrated that the presence of inducible lymphoid follicles, also termed inducible BALT (iBALT), correlates with protection from TB (33). Animals with LTBI harbor greater areas of iBALT within lung lesions relative to animals with ATB, in which BALT was replaced by neutrophils (34). In our current study, nonreactivators often formed multiple, well-organized areas of lymphoid follicles, as observed by H&E staining, as well as by chromogenic staining against CD20 (Fig.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…We have previously demonstrated that the presence of inducible lymphoid follicles, also termed inducible BALT (iBALT), correlates with protection from TB (33). Animals with LTBI harbor greater areas of iBALT within lung lesions relative to animals with ATB, in which BALT was replaced by neutrophils (34). In our current study, nonreactivators often formed multiple, well-organized areas of lymphoid follicles, as observed by H&E staining, as well as by chromogenic staining against CD20 (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Previously, we have shown that increased BALT presence was associated with increased protection in mice, NHPs, and humans (33,34). More importantly, protective immunity to TB, induced by a novel vaccine, also correlated strongly with the presence of BALT (14).…”
Section: Discussionmentioning
confidence: 73%
“…We show that an outcome of S. mansoni infection and the induction of type 2 granulomas within the Mtb-infected lung is the reduced formation of lymphoid follicle-containing granulomas in helminth/Mtb-coinfected hosts and increased accumulation of inflammatory granulocytes. In addition, using Mtb-infected genetically diverse mice, which exhibit heterogeneity in inflammation and disease severity (14), we demonstrate that exacerbated lung inflammation -even in the absence of helminth coinfection -is associated with increased arginase-1 activity. Importantly, increased arginase-1 activity in the serum of patients with ATB is associated with exacerbated lung inflammatory damage and disease severity.…”
Section: Introductionmentioning
confidence: 81%
“…Our recent studies have demonstrated that, in TB, protective granulomas contain distinct B cell lymphoid follicles harboring T cells and macrophages, while inflammatory granulomas lack well-formed B cell-containing lymphoid follicles and instead contain neutrophils that mediate inflammation (13,14). Thus, we next measured the area occupied by lymphoid B cell follicles and found that S. mansoni coinfection in Mtb-infected mice resulted in decreased and poorly formed B cell follicles ( Figure 2C).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation